In Vitro Inhibitory Activity of Dayak Onion (Eleutherine bulbosa Mill.) Essential Oil Against Klebsiella pneumoniae - Marwan Hermawan; Amanah Amanah; Nurbaiti Nurbaiti (GHMJ (Global Health Management Journal), 2019)
Background: The cases of Klebsiella pneumoniae infection in West Java province is still high. Klebsiella pneumoniae bacterium can produce the Extended Spectrum Beta Lactamase enzyme leading to antibiotics resistant, so it is important to look for natural and inexpensive anô€¦žbioô€¦žc alternatives; one of which is Dayak onion plant (Eleutherine bulbosa Mill). The content found in Dayak onion is believed to inhibit the growth of Klebsiella pneumoniae bacteria. This study aims to determine the effectiveness of Dayak onion essential oil on the growth of Klebsiella pneumoniae bacteria. Methods: This study was an experimental study with a post-test control group design using the culture of Klebsiella pneumoniae on the media Muller Hinton Agar in 7 groups. Groups 1 to 5 (K1 to K5) were given sequentially Dayak Onion essential oil solution in 10% DMSO solvent with concentrations of 50%, 25%, 12.5%, 6.25%, and 3.125%. Group 6 (K6) was positive control (+) with 5 Î¼g Levofloxacin, and Group 7 (K7) was Negative (-) with 10% DMSO. The treatment results were measured by the diameter of the host zone and the collected data were analyzed using One-way ANOVA with appropriate Post hoc analysis. Results: The results showed that that there are differences in each group to inhibit the growth of bacteria (p <0.005). K1 are higher than K2, K3, K4, K5, and K7 with increasing concentrations showed greater inhibiô€¦žon. Levofloxacin (K6) showed the highest inhibitory power. Conclusion: The results showed that that there are differences in each group to inhibit the growth of bacteria (p <0.005). K1 are higher than K2, K3, K4, K5, and K7 with increasing concentrations showed greater inhibition. Levofloxacin (K6) showed the highest inhibitory power. Keywords: Klebsiella pneumoniae, Dayak onion essential oil, bacterial inhibition Received: 26 April 2019 Reviewed: 15 June 2019 Revised: 1 July 2019 Accepted: 12 July 2019 DOI: 10.35898/ghmj-33587